Communication Planning Corporate Social Responsibility (CSR) Program of Pt Trisensa Mineral Utama - Irawati, Sri; Juwita, Rina (International Journal Labs, 2023)
A communication planning for a CSR program is essential to be conveyed appropriately, enabling it to genuinely empower the targeted community, while ensuring good execution, compliance with applicable laws and regulations, long-term sustainability, and consideration of the interests of the community and stakeholders. Often, CSR programs lack long-term orientation and merely spend budgets without providing proper development or guidance. PT Trisensa Mineral Utama, a coal mining company located in Kutai Kartanegara Regency, East Kalimantan, plays a role in implementing such CSR activities, in line with the Ministry of Energy and Mineral Resources Decree No. 1824 of 2018 on Guidelines for Community Development and Empowerment Implementation. The aim of this research is to understand how CSR programs or Community Empowerment Programs (PPM) are planned within a company. The methodology used is qualitative, collecting data through interviews with informants, field research observation, and literature studies. This study finds that PT Trisensa Mineral Utama aligns with Philip Lesly's communication planning model, covering analysis and research, policy formulation, implementation program planning, communication activities, and feedback and evaluation.